Experimental Investigation of Large Area Subwavelength Cavity Antennas With Planar Metamaterials - Wang, Wei; Lu, Guang; Diao, Chao; Zhou, Xiachen; Li, Junyang; Liu, Fen; Du, Guiqiang (Frontiers in Materials, 2022)
We experimentally investigated the large area subwavelength cavity antenna with artificial permeability-negative metamaterials in GHz region. It is demonstrated that this new type of planar metamaterials has better directivity and higher gain with the radiation source using the large non-uniform distributed patch array than that using uniform distributed patch array, where the current distribution of the radiation source satisfies the Chebyshev distribution. The experimental values agreed well with simulated results. This new metamaterial antenna has potential applications in weak microwave signal detection and radio observation fields.